Perforator-based propeller flaps reliability in upper extremity soft tissue reconstruction: a systematic review. (February 2017) - Vitse, J.; Bekara, F.; Bertheuil, N.; Sinna, R.; Chaput, B.; Herlin, C.
Current data on upper extremity propeller flaps are poor and do not allow the assessment of the safety of this technique. A systematic literature review was conducted searching PubMed, EMBASE, and the Cochrane Library electronic databases, and the selection process was adapted from the preferred reporting items for systematic reviews and meta-analysis statement. The final analysis included ten relevant articles involving 117 flaps. The majority of flaps were used for the hand, distal wrist, and elbow. The radial artery perforator and ulnar artery perforator were the most frequently used flaps. The were 7% flaps with venous congestion and 3% with complete necrosis. No difference in complications rate was found for different flaps sites. Perforator-based propeller flaps appear to be an interesting procedure for covering soft tissue defects involving the upper extremities, even for large defects, but the procedure requires experience and close monitoring. Level of evidence: II